Psychobehaviorally based features of effective talent development in rugby union: A coach`s perspective - Hill, A.; MacNamara, A.; Collins, D. (The Sport Psychologist, 2015)
Talent development (TD) is widely recognized as a nonlinear and dynamic process, with psychology a key determinant of long-term success in sport. However, given the role that positive characteristics play in the TD process, there is a relative dearth of research examining the psychological characteristics that may derail development. A retrospective qualitative investigation was conducted with academy coaches and directors within rugby union (n = 15), representing nine different elite English rugby union academies, to identify both positive and negative issues that influenced TD. Comprehensive support was found for existing positive constructs as facilitators of effective development. A range of inappropriately applied `positive` characteristics were identified as having a negative impact on development. Potential clinical issues were also recognized by coaches as talent derailers. It is proposed that by incorporating these potentially negative factors into existing formative assessment tools, a more effective development process can be achieved.